Pengaruh kepemilikan instutional, capital intensity dan inventory intensity terhadap Tax Avoidance - Mayang Ratna Sari; I Gede Adi Indrawan (Politeknik Ganesha Medan, 2022)
This study aims to determine the Effect of Institutional Ownership, Capital Intensity, and Inventory Intensity on Tax Avoidance in Consumer Goods Industrial Sector Companies listed on the Indonesia Stock Exchange 2016-2020, with a research sample of 25 companies and using purposive sampling method. The data analysis used is multiple linear regression method and is processed using the application of the Econometric Views (Eviews) version 10 program. The results of this study indicate that the independent variables: (1) Institutional Ownership has no effect on Tax Avoidance. (2) Capital Intensity has an effect on Tax Avoidance. (3) Inventory Intensity has an effect on Tax Avoidance. Meanwhile, together (simultaneously) Institutional Ownership, Capital Intensity, and Inventory Intensity affect Tax Avoidance.